KEMAMPUAN MOTIVASI MEMODERASI PENGARUH KOMPETENSI, KEPEMIMPINAN DAN LINGKUNGAN KERJA PADA KINERJA BENDAHARA DESA DI KABUPATEN TABANAN - Nurhayati, -; Astika, Ida Bagus Putra; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.12.TAHUN 2017, 2017)
Results of previous studies stating that competence, leadership and work environment does not necessarily affect the performance of employees. This study aims to determine the ability to moderate the effect of competence motivation, leadership and environmental performance of Treasurer village in Tabanan. The research was conducted on the entire Treasurer village in Tabanan using primary data obtained from questionnaires distributed to respondents. The sample was selected is a saturated sample in order to obtain as many as 133 respondents. Data analysis was performed by analysis Moderated Regression Analysis (MRA), preceded by a test of validity and reliability and classic assumption test. The results showed (1) the motivation is not able to moderate the influence of competence in the performance of Treasurer village in Tabanan; (2) motivation to be able to strengthen leadership influence on the performance Treasurer village in Tabanan and (3) the motivation is not able to moderate the influence of the working environment on the performance Treasurer village in Tabanan.
Keywords: competence, leadership, work environment, motivation, performance Treasurer Village